1997
DOI: 10.1007/s003840050110
|View full text |Cite
|
Sign up to set email alerts
|

Is mechanical bowel preparation really necessary for elective left sided colon and rectal surgery?

Abstract: The value of mechanical bowel preparation for elective left sided colorectal surgery is debatable. This retrospective study evaluates the incidence of wound infection, wound dehiscence, abdominal/pelvic collections and anastomotic dehiscence between patients who received mechanical bowel preparation [MBP] (n = 61) and those who did not (n = 75). The case notes of 136 consecutive patients undergoing elective left sided colorectal surgery over a three year period in a district general hospital were reviewed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…The policy in our hospital has so far been to use a covering stoma for left-sided traumatic perforations with diffuse fecal peritonitis. However, owing to increased literature of primary anastomosis without a covering stoma [10, 11, 12, 13]and omitting bowel preparation in elective bowel surgery [14, 15, 16, 17], we have changed our policy to favor primary anastomosis without a covering stoma in colonic obstruction and simple perforations with localized peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The policy in our hospital has so far been to use a covering stoma for left-sided traumatic perforations with diffuse fecal peritonitis. However, owing to increased literature of primary anastomosis without a covering stoma [10, 11, 12, 13]and omitting bowel preparation in elective bowel surgery [14, 15, 16, 17], we have changed our policy to favor primary anastomosis without a covering stoma in colonic obstruction and simple perforations with localized peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…They evolved without significant complications and in a low complication rate. Thus, it should be standardize elective colorectal operation without bowel preparation 2,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Parré Ambroise (1510-1590) in his tests showed a high mortality rate as a result of infectious complications in the post-operative period. Only with the advent of antibiotics there was a reduction in morbidity and mortality of these operations 6,8,11 . Over the last few decades, several authors have shown clinical experience of long-term removal of feces from the colon associated with decreased morbidity and mortality in patients undergoing the operation of the colon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted and published along the time worldwide. And today, the reaction of the medical class, based on statistical results, has another conotation [43][44][45][46][47][48] . Studies have also changed and more careful randomization has been a constant concern of the authors, which improves the study quality 49 .…”
Section: Description Of Trialsmentioning
confidence: 99%